Five state factors control progressive stages of freshwater salinization syndrome. Issue 1 (16th March 2022) - Kaushal, Sujay S.; Mayer, Paul M.; Likens, Gene E.; Reimer, Jenna E.; Maas, Carly M.; Rippy, Megan A.; Grant, Stanley B.; Hart, Ian; Utz, Ryan M.; Shatkay, Ruth R.; Wessel, Barret M.; Maietta, Christine E.; et al.
Abstract: Factors driving freshwater salinization syndrome (FSS) influence the severity of impacts and chances for recovery. We hypothesize that spread of FSS across ecosystems is a function of interactions among five state factors: human activities, geology, flowpaths, climate, and time . (1) Human activities drive pulsed or chronic inputs of salt ions and mobilization of chemical contaminants. (2) Geology drives rates of erosion, weathering, ion exchange, and acidification‐alkalinization. (3) Flowpaths drive salinization and contaminant mobilization along hydrologic cycles. (4) Climate drives rising water temperatures, salt stress, and evaporative concentration of ions and saltwater intrusion. (5) Time influences consequences, thresholds, and potentials for ecosystem recovery. We hypothesize that state factors advance FSS in distinct stages, which eventually contribute to failures in systems‐level functions (supporting drinking water, crops, biodiversity, infrastructure, etc.). We present future research directions for protecting freshwaters at risk based on five state factors and stages from diagnosis to prognosis to cure.